PENGEMBANGAN INSTRUMEN PENILAIAN KOGNITIF PADA PEMBELAJARAN MEMBACA PERMULAAN SISWA KELAS I SEKOLAH DASAR - Siti Humaeroh; Yuhana, Yuyu; Sari Dewi, Ratna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to develop a cognitive assessment instrument for beginning reading skills of first-grade elementary school students that is valid and reliable. The research employed the Research and Development (R&D) method through the stages of needs analysis, instrument design, instrument development, expert validation, and instrument testing. The subjects of this study were 25 first-grade students of SDN Sukamanah in the 2025/2026 academic year. The developed instrument consisted of 10 multiple-choice questions designed based on beginning reading indicators and Bloom’s Taxonomy cognitive levels, namely C1 (remembering), C2 (understanding), and C3 (applying). Data collection techniques were carried out through expert validation and student testing. Empirical validity testing used the Pearson Product Moment correlation, while reliability testing used the KR-20 formula. The expert validation results showed a percentage of 90% categorized as very valid. The empirical validity test results indicated that items number 4, 6, 8, and 10 were valid because the calculated r-value was higher than the r-table value. The reliability test obtained a coefficient of 0.76 categorized as high. Based on the results, the cognitive assessment instrument for beginning reading skills was declared valid and reliable, making it feasible to be used as an evaluation tool for first-grade elementary school students.